New Perspectives on Environmental Justice : Gender, Sexuality, and Activism - Yates, Gayle Graham; Verchick, Robert; Unger, Nancy; Sze, Julie; Sturgeon, Noel; Stein, Rachel; Stein, Rachel; Prindeville, Diane-Michele; Plevin, Arlene; Newman, Marcy Knopf; Lucas, Anne; LaDuke, Winona; et al. (Book collections on Project MUSE., 2004)
Women make up the vast majority of activists and organizers of grassroots movements fighting against environmental ills that threaten poor and people of color communities. New Perspectives on Environmental Justice is the first collection of essays that pays tribute to the enormous contributions women have made in these endeavors. The writers offer varied examples of environmental justice issues such as children's environmental health campaigns, cancer research, AIDS/HIV activism, the Environmental Genome Project, and popular culture, among many others. Each one focuses on gender and sexuality as crucial factors in women's or gay men's activism and applies environmental justice principles to related struggles for sexual justice. The contributors represent a wide variety of activist and scholarly perspectives including law, environmental studies, sociology, political science, history, medical anthropology, American studies, English, African and African American studies, women's studies, and gay and lesbian studies, offering multiple vantage points on gender, sexuality, and activism. Feminist/womanist impulses shape and sustain environmental justice movements around the world, making an understanding of gender roles and differences crucial for the success of these efforts.